Simulation LAN and WLAN using the software NS-2 - Eslava Blanco, Hermes Javier; Clavijo Bohorquez, Edisson Walter; Parra Salinas, Edgar Alexander (Visión electrónica, 2014)
This paper shows the development of simulation software in the network Network Simulator (NS-2), was performed three scenarios simulating three scenarios LAN and WLAN, which also assembles a real scenario and one LAN to WLAN compare the results obtained by the NS-2 with respect to the results measured in real world scenarios. Shows the results obtained by the simulator as Throughput, tables of packages for LAN environments, Signal strength and movement of nodes for WLANs.